Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1111/bdi.12096
|View full text |Cite
|
Sign up to set email alerts
|

Overlapping and distinct gray and white matter abnormalities in schizophrenia and bipolar I disorder

Abstract: Background Schizophrenia and bipolar disorder may share common neurobiological mechanisms, but few studies have directly compared gray and white matter structure in these disorders. We used diffusion-weighted magnetic resonance imaging and a region-of-interest based analysis to identify overlapping and distinct gray and white matter abnormalities in 35 patients with schizophrenia and 20 patients with bipolar I disorder in comparison to 56 healthy volunteers. Methods We examined fractional anisotropy within t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
36
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 116 publications
6
36
1
Order By: Relevance
“…In these regions, the micro structural abnormalities were more prominent in the right than in the left hemisphere in patients with BD. The finding of more severe microstructural abnormalities is not consist ent with the results of studies that found lower FA in pa tients with schizophrenia than BD 31,35 or those of studies that found no changes between these groups. 32,33,36 How ever, our finding is similar to that of a study comparing medicationnaive patients with firstepisode BD and schizo phrenia that reported lower FA in the callosal, subcortical and frontooccipital white matter regions in patients with BD.…”
Section: Comparisons Of Lateralization Abnormalities In Patients Withcontrasting
confidence: 86%
See 3 more Smart Citations
“…In these regions, the micro structural abnormalities were more prominent in the right than in the left hemisphere in patients with BD. The finding of more severe microstructural abnormalities is not consist ent with the results of studies that found lower FA in pa tients with schizophrenia than BD 31,35 or those of studies that found no changes between these groups. 32,33,36 How ever, our finding is similar to that of a study comparing medicationnaive patients with firstepisode BD and schizo phrenia that reported lower FA in the callosal, subcortical and frontooccipital white matter regions in patients with BD.…”
Section: Comparisons Of Lateralization Abnormalities In Patients Withcontrasting
confidence: 86%
“…26 The DTI studies directly comparing white matter between patients with schizophrenia and BD have so far yielded in consistent findings, with several studies showing no differ ences [31][32][33][34] and others finding distinct differences between the disorders. 15,35,36 The inconsistent findings could be explained by participant inhomogeneity. One study focused on first episode patients, 15 while others included patients with BDI with and without psychosis, 33,35 or did not specify whether the participants with BD had history of psychosis.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Reductions in all three dMRI indices, MD, AD and RD, have not been reported in patients with schizophrenia. Diffusivity increase is usually observed with increasing neurodegeneration, as reported in demyelinating diseases (Senda et al 2012; Della Nave et al 2004), but also in schizophrenia and bipolar disorder (Anderson et al 2013; Clemm von Hohenberg et al 2014). Reductions in MD, AD, and RD are usually observed in typically developing children and adolescents over the course of the first two decades of life (Lebel and Beaulieu 2011; Lebel et al 2012), which may suggest that changes in the dMRI measures observed here in 22q11DS might be a consequence of abnormal development, rather than the pathology observed in full blown psychosis.…”
Section: Discussionmentioning
confidence: 86%